The Evolutionary Process of Growth and Development of a Business - Yoseph Kristianto (Enigma Institute, 2023)
The evolutionary progression of a business refers to the entire trajectory of the business from its initial inception to its ultimate stage in the life cycle. This process includes a number of important steps, such as coming up with the idea for the business, its initial growth, maturation, adjustment, and innovation, as well as changes in management and ownership, navigating through economic downturns or crises, and making the final decisions about things like succession, divestment, or shutting down. Businesses must consistently demonstrate adaptability, flexibility, and responsiveness to changes in the market, environment, and technology throughout their existence. The success of a firm during its evolution hinges on its capacity to capitalize on opportunities, surmount obstacles, and fulfill client demands while ensuring enduring viability and expansion.